Near field radiative heat transfer between two nonlocal dielectrics. (March 2015) - Singer, F.; Ezzahri, Y.; Joulain, K.
Abstract: We explore in the present work the near-field radiative heat transfer between two semi-infinite parallel nonlocal dielectric planes by means of fluctuational electrodynamics. We use a theory for the nonlocal dielectric permittivity function proposed by Halevi and Fuchs. This theory has the advantage to include different models performed in the literature. According to this theory, the nonlocal dielectric function is described by a Lorenz-Drude like single oscillator model, in which the spatial dispersion effects are represented by an additional term depending on the square of the total wavevector k . The theory takes into account the scattering of the electromagnetic excitation at the surface of the dielectric material, which leads to the need of additional boundary conditions in order to solve Maxwell׳s equations and treat the electromagnetic transmission problem. The additional boundary conditions appear as additional surface scattering parameters in the expressions of the surface impedances. It is shown that the nonlocal modeling deviates from the classical 1 /d 2 law in the nanometer range at distances still larger than the ones where quantum effects are expected to come into play. Highlights: A nonlocal model of the dielectric permittivity is proposed for dielectrics. We calculate the radiative heat transfer (RHT) between two parallel 6H–SiC planes. Saturation of the near-field RHT as the separation distance is reduced. This saturation obtained is in contrary with the local near-field RHT calculations.